Phylogenetic and Functional Biogeographic Approach for Rodent Conservation Across an Environmental Gradient in Chile - Wendy C. Hernández‐Mazariegos; Felipe I. Torres; Reilly Brennan; Luis E. Escobar; R. Eduardo Palma; Christian M. Ibáñez (Journal of Biogeography, 2025)
Aim Understanding how abiotic factors influence species diversity, evolution and functional patterns of species is crucial for biodiversity conservation and for the management of terrestrial protected areas. We evaluate biogeographic and phylogenetic metrics in rodents to understand biodiversity patterns and improve wildlife conservation strategies. Location Chile, South America. Taxon Rodents (Mammalia, Rodentia). Methods We updated the phylogeny of rodent species in Chile using gene sequences retrieved from GenBank. We used the phylogenetic tree to calculate different biodiversity indices. We analysed Species Richness (SR), observed and standard effect size (SES) of Phylogenetic Diversity (PD), Phylogenetic Endemism (PE), and Functional Diversity (FD) across different ecoregions, climatic regions, and terrestrial protected areas along gradients of temperature and precipitation. Results We found high rodent diversity in north and central‐south Chile, and an association between phylogenetic and functional indices. Diversity indices (SR, SES.PD, SES.PE, SES.PE) were strongly associated with ecoregions, with the highest indices occurring in a high‐altitude ecoregion (i.e., Puna), Polar climatic region, and unprotected areas. Main Conclusions Spatial congruence among diversity indices suggests that species composition and evolutionary history play a fundamental role in structuring rodent species assemblages. Areas with high diversity indices delineate regions with high species richness that experience higher species diversification (PD), leading to ecological specialisation (FD) and endemism (PE). The linkages between diversity indices and ecoregions suggest that environmental heterogeneity within ecoregions drives variation in community composition. Environmental variation may be more pronounced in harsh habitats (e.g., Atacama Desert), while weak in benign habitats (e.g., Puna). The spatial mismatch between biodiversity hotspots and protected areas suggests that key evolutionary and ecological processes could be occurring outside current protected areas, raising concerns about the effectiveness of biodiversity conservation strategies.